UV arrows descend from above: lessons from a mass media campaign to improve sun protection behaviours among young adults - Cameron Sugden; Shamieka Dubois; Philippa Maynard; Nicola Scott; Alexis Le Clerc; Matthew Clarke; Sarah McGill; Tracey A O'Brien (Sax Institute, 2024)
Objective: More than 95% of melanomas in Australia are caused by UV radiation from the sun. Young adults are particularly at risk, with 18-24-year-olds spending more time in the sun and protecting their skin less than older adults. A new mass media campaign was delivered in New South Wales, Australia, to motivate this hard-to-reach group to protect their skin from harmful UV radiation. This paper shares learnings from this campaign for public health educators working across diverse fields. Program: Guided by audience research and testing, the campaign combined fear-based and self-efficacy messaging. UV radiation was portrayed as arrows descending from the sky, transforming it into a visible and ever-present threat. High-reach channels such as cinema, outdoor advertising, online videos, audio apps and social media were used to reach the audience. Methods: The campaign was evaluated through an online tracking survey (n = 750, 18-24-year-olds) measuring prompted recognition, message take-out, key diagnostics, and self-reported sun protection intentions and behaviours. Results: The evaluation found that 57% of survey participants recognised the campaign when prompted. Among those that recognised the campaign, 76% said they had used sun protection when outdoors over the summer campaign period (vs 64% of non-recognisers, p < 0.05), and 45% said they had adopted at least three of the five sun protection behaviours (Slip, Slop, Slap, Seek and Slide) 'always' or 'often' (vs. 36% of non-recognisers, p < 0.05). Lessons learnt: A mass-media campaign that aimed to elicit emotional (fear) and cognitive (perceived efficacy) responses and which drew upon social and heuristic cues was associated with greater self-reported sun protection among the target audience. Delivering a combination of message strategies simultaneously within a campaign tailored to young adults may be more effective than adopting a more singular focus.